PENGARUH PEMBELAJARAN BERBASIS PROYEK TERHADAP MINAT WIRAUSAHA SISWA SMK NEGERI 7 BONE (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The influence of project-based learning on students' interest in entrepreneurship. The method used is quantitative with an experimental technique. Data collection was carried out using a questionnaire distributed to 17 samples. The results of the study showed that 14 students were categorized as strongly agree with a percentage of 82.4% and 3 students were categorized as agree with a percentage of 17.6%, and there were no students in the categories of less agree, disagree, and strongly disagree. Thus, this study can be concluded that there is a significant influence of project-based learning on the entrepreneurial interest of XI DKV class students at SMK Negeri 7 Bone.